2018
DOI: 10.1021/acs.energyfuels.8b02780
|View full text |Cite
|
Sign up to set email alerts
|

Low-Concentration CO2 Capture from Natural Gas Power Plants Using a Rotating Packed Bed Reactor

Abstract: A rotating packed bed (RPB) was employed as a highly effective reactor to intensify CO 2 capture in a green and natural amino acid salt absorbent, potassium sarcosine (KSAR), from the flue gas containing a low CO 2 concentration. Experimental results show that a good CO 2 capture performance, presented in terms of CO 2 capture efficiency and overall volumetric mass transfer coefficient (K G a), can be obtained at a low CO 2 concentration of 2−6%. CO 2 capture efficiency could reach higher than 80% at a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Conventional CO 2 chemical absorption processes with packed beds (PB) require excessive packing volume in the CO 2 absorber due to the large mass transfer resistance across the gas–liquid interface . As a process intensification alternative to PB, rotating packed beds (RPB) have been experimentally investigated by many researchers for their use in CO 2 capture with chemical absorption. Moreover, extensive process simulation efforts for CO 2 capture with RPB have been reported to capture process fundamentals of CO 2 chemical absorption and to predict CO 2 removal efficiency. , …”
Section: Introductionmentioning
confidence: 99%
“…Conventional CO 2 chemical absorption processes with packed beds (PB) require excessive packing volume in the CO 2 absorber due to the large mass transfer resistance across the gas–liquid interface . As a process intensification alternative to PB, rotating packed beds (RPB) have been experimentally investigated by many researchers for their use in CO 2 capture with chemical absorption. Moreover, extensive process simulation efforts for CO 2 capture with RPB have been reported to capture process fundamentals of CO 2 chemical absorption and to predict CO 2 removal efficiency. , …”
Section: Introductionmentioning
confidence: 99%
“…7), generally referred to as HIGEE. This technology uses centrifugal fields to form highly sheared thin films where highly efficient gasliquid mass transfer can occur [34], resulting in equipment volume reduction, improve efficiency [52] and safety owing to its high gas-liquid contact area and compactness. With its intense fluid dynamics and mass transfer, low absorbent concentrations can be used in RPBs to achieve similar performance to that of a large conventional absorber column.…”
Section: Rotating Packed Bed Absorbersmentioning
confidence: 99%
“…Chamchan et al [53] observed that both the RPB and conventional packed bed absorbers demonstrated similar absorption performance and energy consumption in CO 2 capture at pilot scale but the RPB was associated with a 1/3 volume reduction compared to the conventional packed bed. In CC from flue gas with low CO 2 concentration, Xie et al [52] demonstrated the RPB to be capable of achieving a mass transfer coefficient around 2.7x higher than in a packed column, with a corresponding 2.6x reduction in equipment volume. Mass transfer rates are greatly affected by gas-liquid contact area influenced by the packing type used in RPBs, with blades [39] and structured [54].…”
Section: Rotating Packed Bed Absorbersmentioning
confidence: 99%
“…A rotating packed bed (RPB) is a typical high-gravity device with efficient gas–liquid contact . In an RPB, small liquid elements like films, filaments, and droplets are obtained by the rotary motion of the rotor, which brings on a large gas–liquid interface area and fast surface renewal frequency, and thus significantly enhances mass transfer and mixing . So far, RPB has been applied in CO 2 absorption and wastewater treatment .…”
Section: Introductionmentioning
confidence: 99%
“…22 In an RPB, small liquid elements like films, filaments, and droplets are obtained by the rotary motion of the rotor, which brings on a large gas−liquid interface area and fast surface renewal frequency, and thus significantly enhances mass transfer and mixing. 23 So far, RPB has been applied in CO 2 absorption 24 and wastewater treatment. 25 A rotating zigzag bed (RZB) is an improved high-gravity device with a zigzag channel in the rotor.…”
Section: Introductionmentioning
confidence: 99%